1999
DOI: 10.1111/j.1834-7819.1999.tb00208.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the Nd:Y AG laser on amalgan dental restorative material

Abstract: The Nd:YAG laser has been marketed as an instrument for use on both hard and soft dental tissues. Its potential for use on hard tissues is limited but it may be the instrument of choice for use in certain soft tissue procedures. The aim of this study was to examine the effects of the Nd:YAG laser on amalgam restorations which are frequently placed on tooth surfaces adjacent to areas of soft tissue which may be subjected to the laser. The amalgam used was Tytin. The laser firing was controlled by a computer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Er:YAG laser has the ability to ablate amalgam surfaces. It increases the surface area by creating crater-like scratches that are 100 μ m in diameter [ 102 , 103 ]. In one in vitro study, laser treatment with Er, Cr:YSGG was found to be a suitable alternative and produced higher SBSs than air-abraded amalgam [ 104 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Er:YAG laser has the ability to ablate amalgam surfaces. It increases the surface area by creating crater-like scratches that are 100 μ m in diameter [ 102 , 103 ]. In one in vitro study, laser treatment with Er, Cr:YSGG was found to be a suitable alternative and produced higher SBSs than air-abraded amalgam [ 104 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They reported that amalgam is ablated by this laser system (6). Er:YAG laser system, with or without water, can ablate amalgam, and the presence of water does not de-crease the efficiency of ablation, though it prevents temperature rise (7). The mechanisms of both Er,Cr:YSGG and Er:YAG lasers are similar (17).…”
Section: Discussionmentioning
confidence: 99%
“…Despite favorable results for bond strength in the laser group, it should be remembered that the dental amalgam is an alloy of mercury with other metals; a small amount of un-reacted mercury is present in the unset amalgam structure, which increases the possibility of mercury vapor release during the ablation process, threatening the dental staff health (7). Although in the present study temperature rise and its side effects were low as a result of a change in the delivery system and use of water spray (18-20), measurement of the mercury vapor released is suggested when using Er,Cr:YSGG laser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite surface evaluation, mercury vapor release during laser ablation should be considered as a hazardous factor for dental staffs. 13 Further studies are needed to assess the bond strength of orthodontic brackets to amalgam restorations besides mercury vapor release and thermal changes evaluation.…”
Section: Discussionmentioning
confidence: 99%